Interaction of Serum Copper and Neurometabolites on Executive Dysfunction in Unmedicated Patients With Major Depressive Disorder - Liao, Xiaoxiao; Lai, Shunkai; Zhong, Shuming; Wang, Ying; Zhang, Yiliang; Shen, Shiyi; Huang, Hui; Chen, Guanmao; Chen, Feng; Jia, Yanbin (Frontiers in Psychiatry, 2021)
Objective: The mechanism of executive function (EF) impairment in major depressive disorder (MDD) remains unclear. Previous studies have demonstrated that altered serum copper levels and neurometabolic alterations may be associated with the psychopathology and cognitive impairment of MDD. While, their inter-relationships in MDD remain uncertain. The present study aims to assess whether the interaction between serum copper levels and neurometabolic alterations is involved in the deficit of executive function (EF) in patients with unmedicated MDD. Methods: Serum copper levels and EFs were measured in 41 MDD patients and 50 control subjects. EFs were evaluated by Trail Making Test, Part-B (TMT-B), Digit Symbol Substitution Test (DSST), Wisconsin Card Sorting Task (WCST), and Semantic Verbal Fluency testing (SVFT). Additionally, 41 patients and 41 healthy controls underwent proton magnetic resonance spectroscopy (1 H-MRS) to obtain ratios of N-acetyl aspartate to creatine (NAA/Cr) and choline-containing compounds to creatine (Cho/Cr) in the lenticular nucleus (LN) of basal ganglia (BG). Finally, association and interaction analysis were conducted to investigate their inter-relationships. Results: The results showed that patients performed worse in the DSST, WCST, TMT-B time and SVFT. Moreover, patients had higher serum copper levels, but lower NAA/Cr ratios in left LN of BG than healthy controls. In patients, serum copper levels were found to significantly negative associated with Categories Completed (CC) number of WCST ( r = -0.408, p = 0.008 ), and positive associated with the Total Errors (TE) and Nonperseverative Errors (PE) number of WCST ( r = 0.356, p = 0.023; r = -0.356, p = 0.022). In addition, the NAA/Cr ratios of left LN were found to significantly negative associated with VFS ( r = -0.401, p = 0.009), as well as negative associated with serum copper levels ( r = -0.365, p = 0.019). Finally, the interaction between copper and NAA may as influencing factors for SVFT and CC number of WCST in patients.. Conclusion: Our results indicated that the interaction of abnormal copper levels and NAA/Cr neurometabolic disruption of the LN may impact executive dysfunction, and this may relevant to the pathophysiology of executive impairment in MDD patients.